InclusiveWeb : A Smart Browser Approach to Enhancing Web Accessibility for Users with Diverse Disabilities - Karthikeyan Dhanasekaran, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article presents InclusiveWeb, an innovative accessibility-focused web browser designed to enhance digital inclusion for users with diverse disabilities. The browser addresses the persistent challenge of widespread non-compliance with web accessibility standards by implementing real-time content adaptation mechanisms, disability-specific tools, and a highly customizable user interface. InclusiveWeb's architecture incorporates advanced machine learning algorithms to dynamically modify web content, offering tailored solutions for users with visual impairments, dyslexia, language disorders, cognitive disabilities, and ADHD. The article details the browser's design principles, technical considerations, and user experience features, supported by a comprehensive evaluation methodology involving user studies with various disability groups. Results demonstrate significant improvements in task completion rates, user satisfaction, and overall accessibility compared to standard browsers. While acknowledging limitations and areas for future research, this article highlights InclusiveWeb's potential to revolutionize web accessibility, shifting the paradigm from reliance on content creators' compliance to browser-level adaptations. The implications of this approach for web accessibility standards, digital inclusion, and future technological developments are discussed, emphasizing the browser's role in creating a more equitable digital landscape.
Keywords: Adaptive Web Browser; Inclusive Design; eal-time Content Adaptation; Disability-Specific Accessibility; Digital Inclusion; Accessibility Browser; ADA Compliance; WCAG; Accessible Web Browser; Ally Browser